NATIONAL PSYCHOLOGICAL FEATURES OF FOREIGN STUDENTS AND THE STYLE OF PEDAGOGICAL COMMUNICATION - I. Angelova (Trakia Journal of Sciences)
The paper considers that the pedagogical communication in a foreign audience is a specific form of interaction between the subjects of intercultural communication a teacher and a student. It is formed on the basis of proficiency of the teacher of special communication technology, depends on his pedagogical mastery and is aimed at education, upbringing and development of the foreign students. It also has reserved for improving the educational process and developing the foundations of intercultural competence for both the student and the teacher. The author points out that the organization of professional pedagogical communication with foreign students requires the teacher to improve his psychological and pedagogical training and sufficient theoretical knowledge in the field of ethnopsychology and ethnopedagogy. Тhe paper analyzes some of the most important national psychological features of the foreign students and their relation to the pedagogical communication.